Peran Kegiatan Ekstrakurikuler Pramuka dalam Pembentukan Karakter Siswa di SMAN 8 Gowa (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the role of Scouting extracurricular activities in character building of students at SMAN 8 Gowa through a descriptive qualitative approach with a literature review method. Data were obtained from various secondary sources in the form of scientific journals, books, and previous research relevant to character education and Scouting activities. The analysis was conducted using content analysis and thematic analysis techniques to identify patterns of values, social interactions, and Scouting symbols that contribute to the formation of student character. The results of the study indicate that Scouting activities are effective in instilling the values of discipline, responsibility, cooperation, leadership, and social awareness through structured activities such as routine training, field activities, and camping. In addition, the process of character building takes place through symbolic interaction as explained in George Herbert Mead's Symbolic Interactionism theory, where symbols, rules, and group dynamics play an important role in developing the "I", "Me", and "generalized other" aspects of students. Thus, Scouting activities have a significant contribution in strengthening character education in the school environment.